Final year students' perception on generic skills upon graduating - Saidi, S. B. (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Soft skills become an important element in national education to achieve global status. This study was conducted to examine the perception of 4th Year School of Education students of Universiti Teknologi Malaysia on soft skills. This study was conducted on 4th year students, Department of Technical Education and Engineering School of Education, Universiti Teknologi Malaysia, Skudai. A total of 180 students were selected based on random stratified sampling method as respondents in this study. Questionnaire is used as the research instrument. Data collected were analyzed by using SPSS version 25.0, to get the mean value, frequency, percentage and standard deviation in descriptive form. Overall, the results of this study found that the perception of 4th year students of UTM School of Education on soft skills was high. The findings also found that the most dominant element of soft skills dominated by students was communication skills and teamwork skills. Both of these skills are the dominant elements that can be mastered because share the same mean value of 4.37. However, there are some aspects that are seen as weaknesses of students such as the mastery of entrepreneurship skills. Hence, institutions and students need to take note to ensure that quality graduates are born from the aspect of soft skills.